Síntese e aplicação de nanopartículas de CdS/ZnS como camada LDS em dispositivo fotovoltaico orgânico - Aoki, Roberto Masahiko (2019)
The present work begins with a bibliographical review on the fundamental concepts regarding the displacement of electrons through the light observed by Hertz and Lenard known as photoelectric effect and the phenomenon of current generation through the illumination of electrodes in an electrolytic solution called photovoltaic effect . The review advances by addressing the electrical and optical properties of the materials used in photovoltaic devices and ends by conceptualizing quantum dots that have been used as the Ultraviolet (UV) and Luminescence Down Shifting Effect (LDS) filter layer to act as protection against UV radiation and increase the efficiency of an organic device. The active layer used was composed of Poly (3-hexyl) thiophene and 1- (3-methoxycarbonyl) -propyl-1-phenyl- [6,6] C61 (P3HT: PCBM). Cadmium Sulphide Nanocrystals (CdS) were synthesized with times of 180 seconds, 320 seconds and 600 seconds and after being optically characterized the sample with the highest potential to serve as LDS was chosen. However the simulation showed that the use of the sample could lead to a small loss in efficiency compared to the reference. The low efficiency could be related to the common surface defects in semiconductor nanoparticles due to the high surface / volume ratio. The CS nanocrystals of the 320 s sample were passivated by a Zinc Sulphide (ZnS) shell, forming a core / shell structure, the samples were optically characterized and the CdS / ZnS of 120 s was used as the LDS layer. The results showed that the application of CdS / ZnS nanoparticles as LDS layer increased the life expectancy of the organic photovoltaic device.